Efficacy of mindfulness‐based stress reduction in emerging adults with poorly controlled, type 1 diabetes: A pilot randomized controlled trial. Issue 2 (27th December 2018) - Ellis, Deborah A.; Carcone, April I.; Slatcher, Richard; Naar‐King, Sylvie; Hains, Anthony; Graham, Amy; Sibinga, Erica
Abstract : Background/Objective: The negative effects of stress on persons with type 1 diabetes (T1D) are well‐established, but effective interventions to reduce stress among emerging adults with T1D are limited. The study objective was to conduct a pilot randomized controlled trial (RCT) to obtain preliminary data on the efficacy of mindfulness‐based stress reduction (MBSR) to reduce stress and improve diabetes health outcomes in a population of high‐risk, urban emerging adults with poorly controlled diabetes. Methods: Forty‐eight participants aged 16 to 20 years of age with T1D (mean duration = 8 years) were randomly assigned to one of three conditions: MSBR, cognitive‐behavioral stress management (CBSM), or a diabetes support group. Data were collected at baseline, end of treatment, and 3 months after treatment completion. Measures of self‐reported stress and depressive symptoms, diabetes management, and glycemic control were obtained. Results: MBSR was found to reduce self‐reported stress at end of treatment ( P  = 0.03, d  = −0.49) and 3‐month follow‐up ( P  = 0.01, d  = −0.67), but no effects on diabetes management or glycemic control were found. Diabetes support group participants had improved glycemic control at the end of treatment ( P  = 0.01, d  = −0.62) as well as reduced depressive symptoms at 3‐month follow‐up ( P  = 0.01, d  = −0.71). Conclusions: Results provide preliminary support for the efficacy of MBSR to improve psychosocial adjustment in emerging adults with poorly controlled T1D but require replication in adequately powered studies. Findings also support the value of peer support in improving health outcomes in this age group.